2008
DOI: 10.1158/1541-7786.mcr-08-0240
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Temozolomide Cytotoxicity by Poly(ADP)Ribose Polymerase Inhibitor ABT-888 Requires a Conversion of Single-Stranded DNA Damages to Double-Stranded DNA Breaks

Abstract: Poly(ADP-ribose) polymerase (PARP) senses DNA breaks and facilitates DNA repair via the polyADP-ribosylation of various DNA binding and repair proteins. We explored the mechanism of potentiation of temozolomide cytotoxicity by the PARP inhibitor ABT-888. We showed that cells treated with temozolomide need to be exposed to ABT-888 for at least 17 to 24 hours to achieve maximal cytotoxicity. The extent of cytotoxicity correlates with the level of double-stranded DNA breaks as indicated by ;H2AX levels. In synchr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 40 publications
4
59
0
Order By: Relevance
“…The preclinical activity of several of these compounds has been described in detail (7)(8)(9)(10). As expected, these agents interfere with the base excision DNA repair (BER) process, leading to enhanced tumor cell killing when administered in combination with various types of DNA-damaging agents (7)(8)(9)11). In particular, PARP inhibitors have been shown to significantly enhance the activity of alkylating agents such as temozolomide in multiple tumor types, due to the importance of BER in repairing adducts formed by these agents (8,11).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The preclinical activity of several of these compounds has been described in detail (7)(8)(9)(10). As expected, these agents interfere with the base excision DNA repair (BER) process, leading to enhanced tumor cell killing when administered in combination with various types of DNA-damaging agents (7)(8)(9)11). In particular, PARP inhibitors have been shown to significantly enhance the activity of alkylating agents such as temozolomide in multiple tumor types, due to the importance of BER in repairing adducts formed by these agents (8,11).…”
Section: Introductionmentioning
confidence: 84%
“…Temozolomide is a monofunctional DNA alkylating agent that induces DNA damage requiring BER-mediated repair and is used for the treatment of melanoma and glioma. Numerous preclinical studies have shown the ability of PARP inhibitors to potentiate the activity of temozolomide in both in vitro and in vivo model settings (7,8,11). This activity is particularly pronounced when used in tumors defective in DSB repair (8,31).…”
Section: Combination Activity With Temozolomidementioning
confidence: 99%
See 1 more Smart Citation
“…PARP targets proteins that facilitate DNA repair of single-stranded or double-stranded DNA breaks (27). If PARP-1 is inhibited, single-strand breaks become double-strand breaks and cell apoptosis occurs during DNA replication (28,29). Therefore, we plan to study temozolomide in combination with the PARP inhibitor ABT-888.…”
Section: Discussionmentioning
confidence: 99%
“…5, 6). Single-strand breaks induced by endogenous DNA damage, radiation, or alkylation can become lethal double-strand breaks (DSB) during replication if PARP is inhibited (7,8) and the accumulation of DSBs acts as triggers of cell death. Thus, the use of PARP inhibitors to enhance DNA-damaging agents, such as TMZ, is being evaluated in the clinic and shows promise as a therapeutic…”
mentioning
confidence: 99%